If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 79 + -6x = 12x + 21 Reorder the terms: 79 + -6x = 21 + 12x Solving 79 + -6x = 21 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 79 + -6x + -12x = 21 + 12x + -12x Combine like terms: -6x + -12x = -18x 79 + -18x = 21 + 12x + -12x Combine like terms: 12x + -12x = 0 79 + -18x = 21 + 0 79 + -18x = 21 Add '-79' to each side of the equation. 79 + -79 + -18x = 21 + -79 Combine like terms: 79 + -79 = 0 0 + -18x = 21 + -79 -18x = 21 + -79 Combine like terms: 21 + -79 = -58 -18x = -58 Divide each side by '-18'. x = 3.222222222 Simplifying x = 3.222222222
| 5(2+6x)=220 | | 13-10x=208-45x | | -14-7x=10+20 | | 131-8x=7x+19 | | 6(5+x)=48 | | 4x+6=-82-7x | | 3(4x+3)=81 | | -5-6x=11-10x | | 7(10+x)=119 | | 110-3x=5x+14 | | x+2+5x=8 | | -19-5x=9-9x | | 3+3x+6x=93 | | 4x+26=13x-64 | | 4x+26=13x-61 | | 6x+23=16x-67 | | 8x-20=52 | | 3(7x+3)=9 | | 4x+26=13-64 | | 7(3+6x)=441 | | 10+x+4x=15 | | 6x+8+4x=38 | | 8x-26=38 | | f(-1)=x^2-5x | | 3x+32=11x-40 | | 4x+20=13x-88 | | 2(6x+5)=46 | | 6(1+7x)=6 | | 5x+60(4x+5)=200 | | 4x*15=109 | | 5(2+6x)=160 | | 9+7x+4x=20 |